1970
DOI: 10.1002/1097-0142(197012)26:6<1261::aid-cncr2820260613>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of thyroid carcinoma in Graves' disease

Abstract: In a consecutive series of 172 patients with Graves' disease treated by total thyroidectomy, 15 patients (9%) had an associated unsuspected carcinoma. There were 20 patients who had received prior treatment with radioactive iodine; 3 (15%) had carcinoma. The high incidence of thyroid carcinoma found in this series suggests that when surgery is elected as the treatment of choice in any given case of Graves' disease, nothing less than a total thyroidectomy should be performed. This high incidence would further i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
1
17

Year Published

1973
1973
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(59 citation statements)
references
References 10 publications
1
40
1
17
Order By: Relevance
“…expression than papillary hyperplasia of Graves' disease. A relationship has been suggested between Graves' disease and papillary carcinoma of the thyroid (31,32). Approximately 4% of patients with papillary carcinoma have Graves' disease (1), whereas the incidence of Graves' disease in the general population is approximately 2.7% in women and is approximately only one tenth as frequent in men (33).…”
Section: Discusssionmentioning
confidence: 99%
“…expression than papillary hyperplasia of Graves' disease. A relationship has been suggested between Graves' disease and papillary carcinoma of the thyroid (31,32). Approximately 4% of patients with papillary carcinoma have Graves' disease (1), whereas the incidence of Graves' disease in the general population is approximately 2.7% in women and is approximately only one tenth as frequent in men (33).…”
Section: Discusssionmentioning
confidence: 99%
“…All the above data were based on patients treated with subtotal thyroidectomy. However, later studies by Shapiro et al on patients with Graves' disease demonstrated an unsuspected thyroid cancer in 8.7 % of them [ 5 ] . This increase was probably observed due to the fact that the patients were treated with total thyroidectomy; a more intense histological examination of the surgical specimen further increased the chances of diagnosing thyroid cancer [ 6 , 7 ] .…”
Section: Introduction ▼mentioning
confidence: 97%
“…Mazzafferi [6] in his series on the management of solitary thyroid nodules had female to male ratio of 4:1. The average age of 172 patients with thyroid masses reported by Shapiro et al [7] was 36 years. 92% of the thyroid masses presented clinically as solitary nodules affecting predominantly the right lobe of the gland.…”
Section: Discussionmentioning
confidence: 98%